A NEW MODEL FOR ONLINE FOOD ORDERING SERVICE BASED ON SOCIAL NEEDS IN A SHARING ECONOMY - Zhou, Ningchang; Lee, Lai (PEOPLE: International Journal of Social Sciences, 2019)
Based on the business phenomenon of sharing economy, and guided by the Blue Ocean strategy, the researchers present a new online food ordering service model. The researchers conducted literature review to understand the current trend of the business of online food ordering. Through user studies, the life style of the main consumer groups of this business was studied to construct the social needs of the users; then through various design research methods such as the brainstorming method, SET analysis method, and SWOT Analysis, etc., the researchers have found important unmet user needs, and proposed a O2O+C2C online ordering service model with private customization and social functions to meet users’ emotional needs. The design of this new service model is in line with the Blue Ocean strategy. It embodies human care, is innovative and feasible, and can provide new directions for the development of related industries.